2020
DOI: 10.4103/ijmr.ijmr_1678_19
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired bacterial pneumonia in adults: An update

Abstract: Community-acquired pneumonia (CAP) is the prominent cause of mortality and morbidity with important clinical impact across the globe. India accounts for 23 per cent of global pneumonia burden with case fatality rates between 14 and 30 per cent, and Streptococcus pneumoniae is considered a major bacterial aetiology. Emerging pathogens like Burkholderia pseudomallei is increasingly recognized as an important cause of CAP in Southeast Asian countries. Initial manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 90 publications
(125 reference statements)
3
36
1
7
Order By: Relevance
“…The results of the analysis of the clinical course and etiological characteristics of CAP of the examined patients reflect the general trends of the disease, consistent with the literature [1,3,8].…”
Section: Discussion Of Research Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the analysis of the clinical course and etiological characteristics of CAP of the examined patients reflect the general trends of the disease, consistent with the literature [1,3,8].…”
Section: Discussion Of Research Resultssupporting
confidence: 89%
“…Currently, pneumonia ranks 4-5 in the world in the structure of causes of death after cardiovascular and cancer diseases, cerebrovascular pathology, injuries and poisonings, and among infectious diseases take 1st place [1]. The mortality of hospitalized patients with severe disease ranges from 14 to 40 % and increases among patients older than 60 years [2].…”
Section: Introductionmentioning
confidence: 99%
“…This study is the first to describe radiological findings with comorbidities in non-invasive pneumonia associated with 2). This finding is in concordance with the findings of other similar studies from India and worldwide [15,[24][25][26][27][28][29][30]. Indian studies predominantly include subjects from the Northern regions and have reported K. pneumoniae or M. pneumoniae as the second major etiological agents, whereas we observed that H. influenzae was the second major pathogen [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…Community-acquired pneumonia (CAP) is the leading cause of mortality and morbidity with substantial clinical and economic impact. 1 The incidence of pneumonia increases with age, 2 with a 10 times higher hospitalization rate in patients aged 65 years and older (about 2000 per 100,000 per year) than in the younger population. 3 Multiple factors are related to the higher incidence of CAP in the older population, such as comorbidities, nutritional status, weakened immune system and swallowing dysfunction.…”
Section: Introductionmentioning
confidence: 99%